Clinical pharmacology during pregnancy / edited by Donald Mattison, Lee-Ann Halbert. - Mattison, Donald R.; Halbert, Lee-Ann (Academic Press, 2022)
"Clinical Pharmacology During Pregnancy, Second Edition is written for clinicians, physicians, midwives, nurses, pharmacists and other medical professionals involved in the care of women during pregnancy. The book focuses on the impact of pregnancy on drug disposition and includes coverage of treatments for diseases of specific body systems as well as essential content on dosing and efficacy. This update includes substantially expanded sections on the ethics of pharmacological research in pregnancy and physiologic changes, along with new sections on patient reported outcomes in pregnancy, delivery and postnatal care, and the use of pharmacokinetic and pharmacodynamic approaches to estimate maternal, placental and fetal dosing. The broad range of this book encompasses analgesics, antiasthmatics, antidepressants, heart and circulatory drugs, vitamins and herbal supplements, and more. Topics in chemotherapy and substance abuse are also covered, as are research issues, including clinical trial design and ethical considerations "--Publisher's description.